On the Multifunctional Character of Questions: (with special reference to verifying and identifying questions) - Harutyunyan, Gohar; Karapetyan, Sirarpi (Armenian Folia Anglistika, 2010)
The article analyzes the multifunctional nature of questions in modern English. In particular, it offers a semantic and pragmatic examination of verifying and identifying questions. An attempt is made to investigate the additional meanings expressed by verifying and identifying questions and their application in communicative processes where these questions can express various indirect speech acts such as request, offer, invitation, advice, etc.